Pharmacological Treatment of Post-stroke Cognitive Deficits - Berthier, Marcelo; Dávila, Guadalupe; Edelkraut, Lisa; López-Barroso, Diana; Torres-Prioris, María; Tubío Ordóñez, Javier (Neurovascular Neuropsychology: Second Edition, 2023)
Acute damage after stroke may be focal, multifocal, or diffuse and responsible for different post-stroke cognitive deficits (PSCD). Overall, large territorial strokes may cause aphasia (partial or complete loss of language function) when they affect the language-dominant left hemisphere, or neglect (inability to attend, orient, or respond to stimuli presented in the hemispace contralateral to the brain lesion) when the stroke compromises the right hemisphere dominant for spatial attention. Small vessel disease (lesions < 1.5 or 2 cm in diameter) affects deep gray nuclei and white matter of the cerebral hemispheres and brainstem. These lesions are multifocal and/or diffuse (lacunes, white matter lesions, leukoaraiosis) and their strategically placed location or recurrence may induce vascular cognitive impairment (VCI) chiefly characterized by psychomotor slowing and dysexecutive deficits. Although neurorehabilitation is the cornerstone treatment for PSCD, in the past few decades the complementary role of pharmacotherapy to improve PSCD has been highlighted. In this chapter, we review the state-of-the-art of pharmacotherapy for PSCD together with the theoretical rationale for using drugs in three highly prevalent stroke-related conditions, aphasia, neglect and VCI. We also provide some clues for refining and expanding the use of efficacy measures and for establishing a better characterization of responders to treatments. The importance of investigating the potential advantage of drug combination and the remodeling of network architecture promoted by drug treatment are also analyzed.
Keywords: cholinesterase inhibitors; dopaminergic stimulation; glutaminergic systems; neurotransmitter systems; noradrenergic agents; pharmacological treatment; post-stroke cognitive deficits; Scopus(2)